Inclusive look. Diversity as a characteristic - Benítez-Gavira, Remedios; Aguilar-Gavira, Sonia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article stems from an R+D+i research project of the 2017-2020 State Plan. Specifically, we will focus on the first phase of research, whose objective was to analyze, reflect and identify what view exists towards diversity. For this, a qualitative documentary research was carried out. After the results achieved, the need for further training from the educational field and future professionals is perceived with the aim of achieving an inclusive school prepared to attend to diversity.